Supramolecular hydrogel networks formed by molecular recognition of collagen and a peptide grafted to hyaluronic acid. (1st July 2016) - Federico, Stefania; Nöchel, Ulrich; Löwenberg, Candy; Lendlein, Andreas; Neffe, Axel T.
Graphical abstract: Abstract: The extracellular matrix (ECM) is a nano-structured, highly complex hydrogel, in which the macromolecules are organized primarily by non-covalent interactions. Here, in a biomimetic approach, the decorin-derived collagen-binding peptide LSELRLHNN was grafted to hyaluronic acid (HA) in order to enable the formation of a supramolecular hydrogel network together with collagen. The storage modulus of a mixture of collagen and HA was increased by more than one order of magnitude ( G ′ = 157 Pa) in the presence of the HA-grafted peptide compared to a mixture of collagen and HA ( G ′ = 6 Pa). The collagen fibril diameter was decreased, as quantified using electron microscopy, in the presence of the HA-grafted peptide. Here, the peptide mimicked the function of decorin by spatially organizing collagen. The advantage of this approach is that the non-covalent crosslinks between collagen molecules and the HA chains created by the peptide form a reversible and dynamic hydrogel, which could be employed for a diverse range of applications in regenerative medicine. Statement of Significance: Biopolymers of the extracellular matrix (ECM) like collagen or hyaluronan are attractive starting materials for biomaterials. While in biomaterial science covalent crosslinking is often employed, in the native ECM, stabilization and macromolecular organization is primarily based on non-covalent interactions, which allows dynamic changes of the materials. Here, we show that collagen-binding peptides, derived from the small proteoglycan decorin, grafted to hyaluronic acid enable supramolecular stabilization of collagen hydrogels. These hydrogels have storage moduli more than one order of magnitude higher than mixtures of collagen and hyaluronic acid. Furthermore, the peptide supported the structural organization of collagen. Such hydrogels could be employed for a diverse range of applications in regenerative medicine. Furthermore, the rational design helps in the understanding ECM structuring.